Atlas anatômico de Bethylidae (Hymenopetera, Chrysidoidea): diversidade de estruturas e termos dos caracteres fenotípicos. - Lanes, Geane Oliveira de (2013)
The skeletomusculature of the parasitoid wasp family Bethylidae is reviewed. Terms employed for other groups of Hymenoptera are reviewed, and a consensus terminology is proposed. External characters are redescribed and correlated with corresponding apodemes and muscles; their phylogenetic importance is discussed. 456 skeletal structures were termed and defined, from which 133 are newly established or redefined. 69 muscles are examined and homologized with those present in other Hymenoptera taxa.